Bone marrow findings in autoimmune lymphoproliferative syndrome with germline FAS mutation - Xie, Yi (Haematologica, 2017)
Autoimmune lymphoproliferative syndrome is a rare genetic disorder characterized by defective FAS-mediated apoptosis, autoimmune disease, accumulation of mature T-cell receptor alpha/beta positive, CD4 and CD8 double-negative T cells and increased risk of lymphoma. Despite frequent hematologic abnormalities, literature is scarce regarding the bone marrow pathology in autoimmune lymphoproliferative syndrome. We retrospectively reviewed 3l bone marrow biopsies from a cohort of 240 patients with germline FAS mutations. All biopsies were performed for the evaluation of cytopenias or to rule out lymphoma. Clinical information was collected and morphological, immunohistochemical, flow cytometric and molecular studies were performed. Bone marrow lymphocytosis was the predominant feature, present in 74% (23/31) of biopsies. The lymphoid cells showed several different patterns of infiltration, most often forming aggregates comprising T cells in 15 cases, B cells in one and a mixture of T and B cells in the other seven cases. Double-negative T cells were detected by immunohistochemistry in the minority of cases (10/31; 32%); significantly, all but one of these cases had prominent double-negative T-lymphoid aggregates, which in four cases diffusely replaced the marrow space. One case showed features of Rosai-Dorfman disease, containing scattered S-100(+) cells with emperipolesis and double-negative T cells. No clonal B or T cells were detected by polymerase chain reaction in any evaluated cases. Classical Hodgkin lymphoma was identified in three cases. Our results demonstrate that infiltrates of T cells, or rarely B cells, can be extensive in patients with autoimmune lymphoproliferative syndrome, mimicking lymphoma. A multi-modality approach, integrating clinical, histological, immunohistochemical as well as other ancillary tests, can help avoid this diagnostic pitfall. This study is registered at Clinicaltrials.gov ID # NCT00001350